Particle‐To‐Field Energy Conversion Inside a Magnetotail Flux Rope - C. X. Du; H. S. Fu; J. B. Cao; E. Grigorenko; Z. Z. Chen; Z. Wang; Z. Z. Guo; Z. Y. Xu; W. D. Fu (Geophysical Research Letters)
Abstract Magnetic flux ropes (FRs) are commonly observed in the universal plasmas, in which various dynamic processes can be embedded and thus become important places for energy conversion. Previous observations generally suggested that the energy conversion inside FRs is from the field to particles. Interestingly, taking advantage of the Magnetospheric Multiscale mission, we present here a newly observed magnetotail FR with strong particle‐to‐field energy conversion (|E ⋅ J| > 1.5 nW/m3). Meanwhile, we have revealed that such energy conversion is driven by an intense electron‐carried field‐aligned current and parallel electric field. Continually, based on the analysis of the electron velocity distribution functions and the power spectral density of the parallel electric field, we further discuss that the energy conversion probably results in the enhancement of the parallel electric field due to the anti‐parallel electron nonthermal population. This study essentially improves the understanding of the energy conversion inside the magnetotail flux rope.